Are Interpersonal Violence Rates Higher Among Young Women in College Compared With Those Never Attending College?. (May 2016) - Coker, Ann L.; Follingstad, Diane R.; Bush, Heather M.; Fisher, Bonnie S.
Estimates of sexual violence and partner violence rates among young women are generated primarily from college samples. Few studies have data to compare rates among similar-aged women attending college with those who never attended college. This study aims to estimate rates of partner violence by type (sexual, physical, and psychological) and severity (mild, moderate, severe), sexual harassment, and knowing or suspecting that someone put a drug in a drink (drugged drink) among a national sample of 959 young women aged 18 to 24 in an intimate relationship in the past 12 months who were either currently in college (college; n = 272) or never attended college (non-college; n = 687). After adjusting for demographic differences between these two groups, no significant differences were found in rates of sexual partner violence (28.4% non-college, 23.5% college), physical partner violence (27.9% non-college, 26.3% college), psychological partner violence ( M score: 6.10 non-college, 5.59 college), sexual harassment (15.5% non-college, 14.1% college), or drugged drink (8.5% non-college, 7.8% college). Finding high rates of interpersonal violence among young women who are and are not currently attending college indicates the need to target all young adults with violence prevention interventions in educational, workplace, and other community-based settings.